Exploring the relationship between leadership communication style, personality trait and organizational productivity - Solaja, Oludele Mayowa; Idowu, Faremi Elijah; James, Adesina Ekundayo (Serbian Journal of Management, 2016)
In organizational research and practice, prolific communication is significantly linked with quality leadership traits. However, an examination of academic literatures reveal that corporate leaders in contemporary organizations are often faced with the challenge of how to moves smoothly between different communication styles that will help them to communicate clearly articulating ideas and knowledge to co-workers whenever the occasion demands which hindered organizational productivity. Against this background, this study explores the relationship between leadership communication style, personality trait and organizational productivity with a bid to provide ways on how leaders can build different communication styles that will influence employee’s personality traits toward achieving increase productivity. The study utilized cross-sectional survey method. Participants were 112 academic staff of Olabisi Onabanjo University, Ogun State, Nigeria who were selected through multi-stage sampling techniques. Data were collected through structured questionnaire and personal observation. Results show that there exists a connection between leadership communication style and personality trait. Also, the finding revealed that leadership communication style determines organization productivity. More so, the finding established that personality traits and communication styles have combined effect on organizational productivity. The findings were discussed with reference to relevant empirical literatures with recommendations for management practice and future research highlighted.